2008
DOI: 10.1021/ac8010439
|View full text |Cite
|
Sign up to set email alerts
|

Selective Electrochemical Sensing of Glycated Hemoglobin (HbA1c) on Thiophene-3-Boronic Acid Self-Assembled Monolayer Covered Gold Electrodes

Abstract: We report a novel concept of sensing glycated hemoglobin, HbA 1c, which is now the most important index for a long-term average blood glucose level, by first selectively immobilizing it on the thiophene-3-boronic acid (T3BA) self-assembled monolayer (SAM)-covered gold electrode by a selective chemical reaction with boronic acid. HbA 1c thus immobilized is then detected by the label-free electrochemical impedance spectroscopic (EIS) measurements with a redox probe, an equimolar mixture of K 3Fe(CN) 6 and K 4Fe(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(78 citation statements)
references
References 38 publications
2
75
0
1
Order By: Relevance
“…Electrochemical impedance spectroscopy study of Ty based electrode (ITO/GNPs/NiO/poly(PPA)-Ty) EIS is a versatile technique describing the response of an electrochemical process taking place at the electrode solution interface [65]. It has been demonstrated that EIS measurements can provide significantly more sensitive responses than amperometric techniques for the detection of some biomolecules [66,67]. To investigate the dopamine (DP) sensing characteristics of the ITO/GNPs/NiO/poly(PPA)-Ty, EIS was performed in the frequency range 100 mHz to 10 5 Hz.…”
Section: Interfacial Properties Ofmentioning
confidence: 99%
“…Electrochemical impedance spectroscopy study of Ty based electrode (ITO/GNPs/NiO/poly(PPA)-Ty) EIS is a versatile technique describing the response of an electrochemical process taking place at the electrode solution interface [65]. It has been demonstrated that EIS measurements can provide significantly more sensitive responses than amperometric techniques for the detection of some biomolecules [66,67]. To investigate the dopamine (DP) sensing characteristics of the ITO/GNPs/NiO/poly(PPA)-Ty, EIS was performed in the frequency range 100 mHz to 10 5 Hz.…”
Section: Interfacial Properties Ofmentioning
confidence: 99%
“…MPA molecule consisted of a thiol functional group at one end, which provided an excellent affinity to gold, and a carboxylic group at another end, which was suitable for bonding covalently to proteins through peptide bond after an activation procedure. Thiol modification of gold electrode surface for protein immobilization was a well-acknowledged technique (32,33,(36)(37)(38). Typically, 4-8 biosensor were prepared in this immobilization step as a batch for this study.…”
Section: Chemical Immobilization Steps On the Gold Electrode (Aue)mentioning
confidence: 99%
“…This reaction results from the boronic acids hydroxyl groups strong interactions with the diol-containing saccharides, forming cyclic boronic acid esters on complexation. Recently, a number of studies have been made with respect to the selective recognition of saccharides and their detection using boronic acid-diol interactions [8][9][10]. Shoji and Freund reported that using a poly(aniline boronic acid) (PABA) modified electrode, the electrochemical potential was sensitive to sugars, due to the formation of a boronic acid-diol complex that caused the fluctuation of the pKa of PABA [8].…”
Section: Introductionmentioning
confidence: 99%
“…Arimori and co-workers synthesized a novel compound that combined the boronic acid receptor and a pyrene unit into a transducer for a d-glucose fluorescence sensor [9]. Also reported, by Park et al, was a thiophene-3-boronic acid modified gold electrode with selectivity for HbA 1c that employed a quartz crystal [10]. Reddy and co-workers prepared a polyanionic affinity agent, which was used for the measurement of HbA 1c , based on ultraviolet (UV) absorbance [11].…”
Section: Introductionmentioning
confidence: 99%